Lipid exposure leads to metabolic dysfunction in fetal sheep cardiomyocytes - Natasha N. Chattergoon; Karthikeyan Bose; Samantha Louey; Sonnet S. Jonker (Physiological Reports)
Abstract Fetal circulating lipids are low but rise precipitously following birth. It is unknown how prematurely elevated lipids affect the fetal heart, which primarily uses carbohydrates for energy. Fetal sheep were surgically instrumented and received Intralipid 20® or Lactated Ringer's Solution intravenously. After 8 days, myocardial biopsies were taken, and cardiomyocytes were dispersed. Lipid uptake was assessed by labeled saturated long‐chain fatty acids (LCFA) and very long‐chain fatty acids (VLCFA) incorporation. Maximal oxygen consumption rates (OCR) were measured. Gene and protein expression levels were measured by quantitative PCR and Western blotting. Intralipid treatment increased LCFA (p < 0.001) and VLCFA (p < 0.001) lipid droplet number, and LCFA (males p = 0.002) and VLCFA (p = 0.018) droplet size. Fetal Intralipid treatment reduced maximal OCR in basal media (p = 0.005). Palmitic acid decreased maximal OCR regardless of fetal treatment or length of in vitro exposure (p = 0.006). Fetal Intralipid upregulated genes included CD36 (p = 0.001), CPT1A (p < 0.001), CPT1B (p < 0.001), VLCAD (p < 0.001), and PDK4 (p < 0.001), with no differences in protein expression. There were no effects on ER stress, apoptosis, or autophagy markers. Extended elevated lipid levels in the fetus increased lipid uptake and may have shifted substrate preference towards lipids, but all lipid exposure depressed fetal cardiac metabolism. Prematurely elevated lipids mature but suppress oxidative metabolism.